Effect of roller cylindricity error on the stress distribution in multi-layered coatings - Bayrak, Ramazan (PERGAMON-ELSEVIER SCIENCE LTD, 2026)
Analytical studies on the mechanical behavior of multilayer coating systems have generally focused on ideal geometric profiles; however, tolerances arising from manufacturing processes inevitably lead to cylindricity errors. This study aims to fill this gap in the literature by presenting a comprehensive numerical framework that investigates the effect of realistic geometric defects, based on the ISO 12297-1 standard, on mechanical performance. The analyses are performed using an efficient semi-analytical model based on Papkovich-Neuber potentials. The results revealed a critical stress locking mechanism in single-layer stiff coatings. Contrary to general expectations, thickening the stiff coating has not improved performance; instead, it has confined the maximum stress to the interface due to the abrupt change in stiffness. The proposed 10-layer gradually transitioning architecture to overcome this structural constraint reduced the von Mises stress by 20% compared to the single-layer reference model in the most critical error class (Grade G5). More importantly, the gradual stiffness transition (stiffness smoothing) shifted the stress peak away from the interface into the coating, homogenizing the load sharing. This study demonstrates that, in realistic conditions with manufacturing errors, material and thickness selection are not sufficient to mitigate failure risks; the layer architecture must also be tailored.
Keywords: Multilayered coatings; Cylindricity error; Contact mechanics; Subsurface stress; Graded architecture; CONTACT MODEL; LAYER; Mechanics